2000
DOI: 10.1152/ajprenal.2000.278.4.f644
|View full text |Cite
|
Sign up to set email alerts
|

Renal interstitial Ca2+

Abstract: Renal interstitial fluid Ca(2+) concentration ([Ca(2+)](isf)) was measured in anesthetized Wistar rats by using in situ microdialysis. During perfusion of 20 cm of the proximal small intestine with Ca(2+)-free buffer, renal [Ca(2+)](isf) was 1.63 +/- 0.19 mmol/l in the cortex (n = 6) and 1.93 +/- 0.12 mmol/l in the medulla (n = 5, P = 0.223). When Ca(2+) in the intestinal lumen was increased to 3 mmol/l, no change was seen in total or ionized serum Ca(2+) (S(Ca)), urinary Ca(2+) excretion (U(Ca)), or Ca(2+) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 23 publications
2
33
1
Order By: Relevance
“…Mupanomunda et al (25) has shown that renal cortical interstitial calcium concentration may actually vary normally over surprisingly wide ranges, consistent with the concentrations we have used. Thus, our observations suggest that PDE1C may contribute to the overall balance of cAMP formation in the JG cell under normal physiologic circumstances and that the JG cell CaSR may serve as an important conduit pathway (29), linking changes in the extracellular calcium with a calcium-mediated balance of cAMP metabolism and synthesis within the cell.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Mupanomunda et al (25) has shown that renal cortical interstitial calcium concentration may actually vary normally over surprisingly wide ranges, consistent with the concentrations we have used. Thus, our observations suggest that PDE1C may contribute to the overall balance of cAMP formation in the JG cell under normal physiologic circumstances and that the JG cell CaSR may serve as an important conduit pathway (29), linking changes in the extracellular calcium with a calcium-mediated balance of cAMP metabolism and synthesis within the cell.…”
Section: Discussionsupporting
confidence: 89%
“…We used both the normal 1.2 mM Ca in the media reflecting normal renal cortical interstitial free Ca concentration (25), as well as a reduced but still physiological Ca concentration of 0.9 mM as an established technique to amplify basal renin release (4) so as to exaggerate any inhibitory response to activation of the CaSR. In each case, compounds were tested using a primary culture of JG cells; either without or after the addition of 1 M of the CaSR agonist cinacalcet (Sensipar; Amgen, Thousand Oaks, CA; n ϭ 16) (28,29).…”
Section: Inhibition Of Pde Activitymentioning
confidence: 99%
“…Bukoski, 2001, unpublished observations), which is well within the range of the concentrations that have been shown to occur in the interstitial fluid compartment of the small bowel 16 and renal cortex. 17 The relaxation is attenuated by sensory denervation and correlates with the presence of Ca 2ϩ receptor-positive nerve fibers. 2 Ca 2ϩ -induced relaxation of rat arteries has also been shown to be inhibited by blockers of the large conductance K Ca channel 4,5 and by SR141716A 4 , a compound with CB 1 antagonist activity.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the CaR has been shown to detect small changes in Ca 2+ e 13 , and small increases in [Ca 2+ ]IF that are within the physiological range 14 . In situ microdialysis studies measuring [Ca 2+ ]IF in the duodenal submucosa and kidney cortex, two tissues that are essential for the regulation of peripheral resistance and blood pressure (BP), showed dynamic changes as a function of the gut lumen [Ca 2+ ].…”
Section: Discussionmentioning
confidence: 99%